GREEN CHEMISTRY ALLIED TO BUSINESS STRATEGY - Plens, Ana Carolina de Oliveira; Monaro, Daniel Luis Garrido; Alves, Maria Rita Pontes Assumpção (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
Developing in a sustainable way is a challenge for companies that priorize productivity and profitability. However, sustainability has beenincorporated into corporate strategies, since the preservation of the environment causes improvement on its image and allows access to globalmarkets that has this aspect as a requirement for their business. The ETHOS Institute, in order to help companies manage their business ina socially responsible manner, has supported many companies to implement initiatives aimed at sustainable development. This article aimsto assess the implementation of corporate social responsibility and competitiveness in the medium-sized fabric dyeing industry, in orderto combine the Green Chemistry to the business strategy. Thus developed a case study of two companies in the dyeing of textiles sector,through the ETHOS Institute adapted questionnaire application, to evaluate their practices aimed at sustainability, “green” practices and thecommitment level with the environment and society preservation. Thus, Company A had few actions in favor of environmental guidelineswhile Company B had some more definite initiatives in this direction. However, it is conclude that companies in the dyeing segment of thetextile industry, analyzed in this article, don’t consider CSR as a competitive resource, with incipient actions in a sustainable developmentpractices, which was evident by the method used to collect data.